Pergaulan Bebas dan Ancamannya bagi Remaja di SMA Negeri 3 Panyabungan - Liantha Adam Nasution; Asrial Harahap; Lanni Jurriah; Nurul Padilah; Sonia Sonia; Nurul Rambe; Renda Zelkasih; Lainatus Sifah; Arda Lestari; Aulia Soraya; Nur Wafiah Nst; Fauziah Hannur; Yuni Sari Nst (Kegiatan Positif : Jurnal Hasil Karya Pengabdian Masyarakat, 2025)
Promiscuity among teenagers is an increasingly worrying issue, especially in high school environments. This service aims to provide education and outreach regarding the dangers of promiscuity to students at SMA Negeri 3 Panyabungan. This activity was carried out through a seminar involving 30 students as representatives from each class and teachers. This seminar presented speakers from STAIN Madina lecturers who discussed the negative impacts of promiscuity and solutions to prevent it. The results of this seminar show an increase in students' understanding of the dangers of promiscuity and their awareness of the importance of maintaining healthy relationships. Therefore, collaboration is needed between schools, teachers and parents in providing guidance to students.